FINANCIAL STATEMENT ANALYSIS AND PERFORMANCE OPTIMIZATION AT THE OFFICE OF PT PERKEBUNAN NUSANTARA MEDAN IV FOR 2018 - 2022 - Dhiftania Luthfiya Azra; Juliana Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
PT Perkebunan Nusantara IV or commonly abbreviated as PTPN IV, is a subsidiary of PTPN III engaged in the agro-industry of palm oil and tea. The purpose of this study is to assess the optimization of the company's financial performance using the Current Ratio, Debt to Equity Ratio, Return On Equity and Total Assets Turn Over. This type of research is descriptive quantitative research using seunder data. The results of the analysis using Current Rsto found that the average value was 119%, but in 2018-2020 it decreased or was in a bad condition, while in 2021-2022 it increased and was in very good condition. The Debt to Equity Ratio in 2018-2022 is very good with an average value of 128%. Return On Equity in an unfavorable condition, namely in 2018-2022 obtained an average value of 21%. Total Assets Turn Over is in excellent condition with an average value of 2.40 times.